Informed, tailored, and targeted pharmacy support for nurses administering medicines in care homes - Gilmartin JFM (Dove Medical Press, 2015)
Julia Fiona-Maree GilmartinResearch Department of Practice and Policy, University College, London School of Pharmacy, London, UKAbstract: Care home nurses could benefit from more informed, tailored, and targeted pharmacy support when undertaking medicine administration. Pharmacists could use the principles of ethnographic research methods to inform, tailor, and target the medicine administration support they provide. It should be determined if existing pharmacy support has been informed following comprehensive observations of care home medicine administration.Keywords: pharmacy, medicine administration, care home, nurses